CHALLENGES, STRATEGIES AND QUALIFICATIONS OF AUDITORS IN THE SOCIETY 5.0 ERA - Riris Rotua Sitorus; Sihar Tambun (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2023)
We will soon live the Era of Society 5.0. An era that is integrated with AI in all professions, including auditors. The research aims to obtain an overview of the auditor's profession in the future. First, the challenges that auditors will face and second, the strategies that auditors need in the Society 5.0 Era. This research uses a literature study approach with content analysis. Data sources from journal articles, proceedings, online news, e-books and YouTube. Data processing consists of four stages, namely data input, coding, visualization, and determining conclusions. Data processing uses the NVivo 12 Plus software. The results of the research succeeded in providing an overview of the six challenges and seven strategies needed to compete in the era of society 5.0. The implication is that the research results can be used as a reference for auditors to prepare themselves for the Era of Society 5.0.